2021
DOI: 10.18231/j.ijca.2021.042
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane block versus wound site infiltration using 0.25% bupivacaine for post-operative analgesia after caesarean delivery performed under subarachnoid block

Abstract: : Transversus abdominis planeTAP) block has been described as an effective technique to reduce postoperative pain after caesarean section. Wound site infiltration (WSI) has been a traditional method for pain relief. In our study we attempt to compare the analgesic effect of TAP block with wound site infiltration after caesarean section. A randomized comparative study was conducted on 60 parturients. Patients were randomized into Group T (TAP block, n=30) and Group I (WSI, n=30). Spinal anaesthesia was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We included 114 trials (8730 women) in our final network analysis, 73 (64%) of which reported the primary outcome of morphine equivalent dose in the first 24 postoperative hours for 5126 (59%) women (Fig. 1 and online Supporting Information, Table S1) [14–127]. Placebo vs. transversus abdominis plane injection in 11 trials was the most common direct comparison.…”
Section: Resultsmentioning
confidence: 99%
“…We included 114 trials (8730 women) in our final network analysis, 73 (64%) of which reported the primary outcome of morphine equivalent dose in the first 24 postoperative hours for 5126 (59%) women (Fig. 1 and online Supporting Information, Table S1) [14–127]. Placebo vs. transversus abdominis plane injection in 11 trials was the most common direct comparison.…”
Section: Resultsmentioning
confidence: 99%